Interpersonal Metadiscourse Markers in the “Monash Life” Magazine - Ayu Kezia Yasinta, Ni Luh Putu (Humanis; Vol 22 No 3 (2018), 2018)
Metadiscourse is a new concept of analyzing the discourse related to the relationship between the writer and reader. This can be the way of communicating used by writer to reader. Interpersonal metadiscourse markers are divided into two broad terms; they are interactive and interactional metadiscourse markers. The aims of this research are to identify and explain the interpersonal metadiscourse markers used in the “Monash Life” magazine. This magazine was chosen because it contains many articles in which the writers convey their opinions. The study used twenty two articles in the magazine. The note taking technique was used as the method of collecting the data. First, the articles were read intensively; second, the phrases or words categorized as the type of interpersonal metadiscourse markers were selected. The qualitative method was used to analyze the data. Every sentence or paragraph which contains the types of interpersonal metadiscourse markers were analyzed and classified. The theory of metadiscourse proposed by Hyland (2005) was used in this study. The result of the analysis shows that there were sixty one data that contain the interpersonal metadiscourse markers in the magazine. There were thirty four data found in the category of interactive metadiscourse markers, and twenty seven data in the category of interactional metadiscourse markers. It could be concluded that the use of interactive metadiscourse markers was more dominant than interactional metadiscourse markers in the Monash Life Magazine.